Substantial regional climate change expected following cessation of CO2 emissions. (1st November 2022) - MacDougall, Andrew H; Mallett, Josie; Hohn, David; Mengis, Nadine
Abstract: The zero emissions commitment (ZEC) is the expected temperature change following the cessation of anthropogenic emissions of climate altering gases and aerosols. Recent model intercomparison work has suggested that global average ZEC for CO2 is close to zero. However there has thus far been no effort to explore how temperature is expected to change at spatial scales smaller than the global average. Here we analyze the output of nine full complexity Earth System Models which carried out standardized ZEC experiments to quantify the ZEC from CO2 . The models suggest that substantial temperature change following cessation of emissions of CO2 can be expected at large and regional spatial scales. Large scale patterns of change closely follow long established patterns seen during modern climate change, with higher variability and more change as one approaches the polar regions, and with more change over land than ocean. The sign of temperature change (warming or cooling) varies by model and climatic zone. At the regional scale patterns of change are far more complex and show little consistency between different models. Analysis of model output suggest that for most models these changes far exceed pre-industrial internal variability, suggesting either higher climate variability, continuing changes to climate dynamics or both. Overall substantial regional changes in climate are expected following cessation of CO2 emissions but the pattern, magnitude and sign of these changes remains highly uncertain.